POTENSI KELELAWAR PEMAKAN BUAH (CHIROPTERA: PTERIPODIDAE) SEBAGAI RESERVOIR LEPTOSPIRA DI PROVINSI JAWA TENGAH - Aryo Ardanto; Muhidin Muhidin; Ayu Pradipta Pratiwi; Dimas Bagus Wicaksono Putro; Esti Rahardianingtyas; Jarohman Raharjo (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2018)
Beside as seed dispersal and high valued plant pollinator, frugivorous bat (Pteripodidae) also has a role as reservoir of Leptospira. This study was aimed to survey the the prevalence of Leptospira among Pteripodidae in three regencies of Central Java Province namely Purworejo, Pati and Pekalongan, and their potential as reservoir of Leptospira. This study used four mist nets and a harp trap to collect bat at each site of each regency which has six sites. The caught bats were identified morphologically and followed by serological examination by Microscopic Aglutinasion Test (MAT). A total of 278 Pteripodidae was examined by MAT consisting of five genera with eight species. The result of MAT for Leptospira showed that there are no examined bats were positif (0%). It indicated there is no sufficient evidence that Pteripodidae as potential reservoir of Leptospira in Central Java.